2017
DOI: 10.1371/journal.pone.0179255
|View full text |Cite
|
Sign up to set email alerts
|

Functional neural circuits that underlie developmental stuttering

Abstract: The aim of this study was to identify differences in functional and effective brain connectivity between persons who stutter (PWS) and typically developing (TD) fluent speakers, and to assess whether those differences can serve as biomarkers to distinguish PWS from TD controls. We acquired resting-state functional magnetic resonance imaging data in 44 PWS and 50 TD controls. We then used Independent Component Analysis (ICA) together with Hierarchical Partner Matching (HPM) to identify networks of robust, funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Secondly, we applied the ICA with HPM-ICA, which we proposed and published previously ( Wang et al, 2011 ; Qiao et al, 2015 , 2017 ), to the preprocessed fMRI data to estimate the brain FC networks. In this method, we used ICA to generate N ICs for each participant and then used partner matching to match these components across the participants, yielding clusters of components that matched across participants.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, we applied the ICA with HPM-ICA, which we proposed and published previously ( Wang et al, 2011 ; Qiao et al, 2015 , 2017 ), to the preprocessed fMRI data to estimate the brain FC networks. In this method, we used ICA to generate N ICs for each participant and then used partner matching to match these components across the participants, yielding clusters of components that matched across participants.…”
Section: Methodsmentioning
confidence: 99%
“…To associate the spatial distribution of the task-based functional networks identified by ICA with resting-state networks, we derived Tanimoto Indices (also known as Jaccard Indices) by comparing each task-based network to all restingstate networks (Wang and Peterson, 2008;Qiao et al, 2017). Overlaps of the top five task-related networks for each group (all participants, AC, AWS) with resting-state networks are presented in Supplementary Tables S1-S3.…”
Section: Independent Component Analysis (Ica)mentioning
confidence: 99%
“…Salmelin et al found that rather than the typical pattern of activity starting in L-IFG, advancing to left lateral central sulcus, and then to the dorsal premotor cortex, AWS had activity first arising in motor cortex prior to L-IFG thus indicating attempts to initiate the motor programs prior to the construction of the articulatory plan. In addition, the front aslant tract (i.e., between Broca's and SMA) has been implicated as a neural correlate of stuttering (Kronfeld-Duenias, Amir, Ezrati-Vinacour, Civier, & Ben-Shachar, 2016;Misaghi, Zhang, Gracco, Luc, & Beal, 2018;Qiao et al, 2017), highlighting the possible dysfunction between planning/execution areas in stuttering speakers. Taken together with previous results from the literature, our findings confirm the importance of the L-IFG for our understanding of stuttering and indicate involvement of neural processes underlying speech-motor planning in the disorder.…”
Section: Neural Correlates Of Planning In Adults Who Stuttermentioning
confidence: 99%